Ferrium steels and other high performance materials for next generation rotorcraft transmissions and applications - Taskin, K. (My University, 2019)
Integrated Computational Materials Engineering (ICME) technologies are effective tools to accelerate implementation of new higher performance alloys, shortening design time and reducing cost compared to empirical methods. Using these technologies and their Materials by Design® approach, QuesTek Innovations LLC has designed, commercialized and deployed a class of high-performance Ferrium steels specifically addressing demanding and critical transmission applications for the global rotorcraft industry. Furthermore, these ICME technologies have been expanded to the field of Additive Manufacturing (AM) to adapt the Ferrium steels and design new alloys specifically tailored to the unique processing conditions to bring advanced capability to the rotorcraft and aerospace industries.